A Novel Highly Efficient Host‐Sensitized Red Emitting (Ba2YV3O11 : Eu3+) Phosphor for Hybrid White LEDs. Issue 17 (5th May 2020) - Rajendran, Marikumar; Vaidyanathan, Sivakumar
Abstract: The present investigation focused on the sequence of Eu 3+ activated red‐emitting vanadate phosphor for the high performance white LEDs. The blue emitting host lattice (Ba2 YV3 O11 ) and red emitting Ba2 YV3 O11 : Eu 3+ phosphors were synthesized by the conventional solid‐state method and studied their optical properties in details. The host lattice and Eu 3+ activated red phosphors were crystallized in the monoclinic crystal system. The Ba2 YV3 O11 emission was found in the bluish‐green region (444 and 512 nm, which corresponds to the 3 T2 → 1 A1 and 3 T1 → 1 A1 transitions), and the Eu 3+ activated phosphors (Ba2 Y1‐x Eux V3 O11, x=0‐1, insteps of 0.1) display intense red emission at 618 nm due to the 5 D0 → 7 F2 electric dipole (ED) transition. The concentration quenching was observed at x=0.6, the detailed energy transfer mechanism was also explored. Thermal stability of the Ba2 Y0.4 Eu0.6 V3 O11 red phosphor retains the ∼60 % emission intensity at 423 K, and the internal quantum efficiency (IQE) was found to be 30 %. The red and white LEDs were fabricated by using the synthesized red phosphor with the combination of near UV LED (n‐UV), the white LED showed white emission with CIE is x=0.359; y=0.395; higher CRI (89) and low CCT (4693 K) values. These results prescribe that the presently synthesized phosphor can act as a suitable red‐emitting component in hybrid white LEDs. Abstract : A novel Ba2 YV3 O11 : Eu 3+ red phosphor was designed and systematically studied their structural and optical properties. The Ba2 YV3 O11 phosphor shows the blue emission, whereas the Eu 3+ activated phosphor showed sharp red emission. The vanadate anion in the participated in the energy transfer process and boost the Eu 3+ emission. The optimized phosphors composition exhibits decent thermal stability and internal quantum efficiency. Besides, the fabricated hybrid white LED shows excellent CRI and CCT values.